Dinâmica espaço-temporal de taxocenoses de crisopídeos (Neuroptera: Chrysopidae) em ecossistemas naturais - Costa, Renildo I. F.; Souza, Brigida; de Freitas, Sergio [UNESP] (Entomological Soc Brasil, 2010)
In order to study the interactions of green lacewings toxocenosis on natural ecossystems, samplings were carried out in the Parque Ecologic Quedas do Rio Bonito, located in Lavras, Alto Rio Grande region, South of Minas Gerais, Brazil. The species inventory was accomplished in two vegetation types: semi-evergreen forest and open field formations, including areas of montane grassland, rocky montane grassland and "cerrado". Insects were captured with a butterfly net during 2h, walking through each vegetation formation. Sampling resulted in 1,948 specimens belonging to 30 species, of which 14 were Chrysopini and 16 Leucochrysini. Representatives of these tribes were observed both in forest and in open field formations. Species of the genera Ceraeochrysa, Chrysoperla, Chrysopodes, Plesiochrysa and Leucochrysa were found in forests and in open field formations, except for Plesiochrysa. The highest richness and diversity of species were observed in the forest. The similarity index among the communities of green lacewings in the studied areas was 27%.
Spatio-Temporal Dynamic of Green Lacewings (Neuroptera: Chrysopidae) Taxocenosis on Natural Ecossystems
Keywords: Biodiversity; taxonomy; predator